A gradient boron nitride / polyimide composite substrate, a preparation method and application thereof

CN122995318APending Publication Date: 2026-10-27SHANGHAI JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182304.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,将其应用于高效率的柔性砷化镓太阳能电池时,面临两个关键瓶颈:1)热膨胀系数(CTE)严重失配:商业聚酰亚胺薄膜的CTE通常高达40-60×10-6/K,而砷化镓材料的CTE约为5.7×10-6/K

Benefits of technology

1、卓越的热机械可靠性:本发明制备的梯度BN/PI复合薄膜,BN纳米片在预设作为器件生长界面的一侧(即靠近GaAs外延层一侧)浓度最高,并向另一侧逐渐降低,其高BN含量侧的热膨胀系数可显著降低,通过这种梯度过渡的CTE设计,相比Janus结构的突变界面,能更平缓地释放GaAs外延层与聚合物衬底之间的热应力,从根本上降低柔性砷化镓太阳能电池在热循环中界面开裂的风险,大幅提升器件的环境耐受性与服役寿命。同时,柔性侧的BN浓度低,保留了聚酰亚胺的良好柔韧性,使整个衬底“刚柔并济”。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995318A_ABST
    Figure CN122995318A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of gradient boron nitride / polyimide composite substrate and its preparation method and application.The present application is by using stainless steel ball milling beads in alkali environment, so that boron nitride nanosheet generates magnetic iron oxide / boron nitride composite magnetic nanosheet in ball milling process, realize the hydroxylation and magnetization of boron nitride nanosheet, and under the induction of magnetic field, nanosheet forms the concentration gradient distribution from one side to the other side in film interior, forms gradient boron nitride / polyimide composite substrate.The composite substrate has good mechanical property, flexibility, thermal conductivity and low thermal expansion coefficient, so that it is used for flexible GaAs battery substrate, can significantly improve the thermal matching with GaAs epitaxial layer and the heat dissipation capacity of device, to improve the reliability and service life of battery.Compared with unmagnetized boron nitride nanosheet scheme, the present application gradient boron nitride / polyimide composite substrate further reduces the thermal expansion coefficient while improving the thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-performance flexible polymer composite materials technology, and relates to a gradient boron nitride / polyimide composite substrate, its preparation method, and its applications, particularly a boron nitride / polyimide composite thin film with a gradient distribution structure. This thin film is particularly suitable as a substrate for flexible gallium arsenide (GaAs) solar cells, solving problems such as epitaxial layer cracking and decreased reliability caused by thermal expansion mismatch. Background Technology

[0002] Polyimide (PI) films are considered ideal substrate materials for next-generation flexible electronic devices due to their excellent flexibility, high-temperature resistance, and good insulation properties. However, their application in high-efficiency flexible gallium arsenide solar cells faces two key bottlenecks: 1) Severe mismatch in coefficient of thermal expansion (CTE): The CTE of commercial polyimide films is typically as high as 40-60 × 10⁻⁶. -6 / K, while the CTE of gallium arsenide materials is approximately 5.7 × 10⁻⁶. -6 / K. This huge difference generates enormous thermal stress during battery fabrication (high-temperature process) and operation (temperature cycling), which can easily lead to cracking and peeling of the brittle GaAs epitaxial layer, causing battery failure. 2) Insufficient thermal management capability: Polyimide itself has low thermal conductivity (<0.2 W / (m·K)), which is not conducive to the rapid dissipation of heat generated during GaAs battery operation, resulting in increased battery junction temperature, which in turn causes a decrease in conversion efficiency and a reduction in battery life.

[0003] To reduce the core-effect transfer (CTE) of polyimide (PI) and improve its thermal conductivity, existing techniques typically incorporate low-expansion, high-thermal-conductivity nanofillers such as boron nitride (BN) into the PI matrix. However, while high filler loading (typically >20 wt%) can significantly improve thermal properties, it severely compromises the film's flexibility, light transmittance, and mechanical strength. Furthermore, simple blending or symmetrical composite structures struggle to simultaneously meet the contradictory requirements of "low CTE at the interface matched with GaAs" and "maintaining good overall flexibility" at low average filler content.

[0004] A review of existing technologies revealed that Professor Shuhong Yu's research group at the University of Science and Technology of China, in an article published in *Advanced Materials*, Volume 34, page 2105-299, proposed the fabrication of polyimide composite films using a double-layer spraying technique. These films exhibit an asymmetric structure with one side rich in filler, significantly improving the mechanical properties of the films. However, this structure suffers from abrupt physical interface changes between the filler layer and the pure polymer layer, potentially leading to stress concentration at the interface. Furthermore, the coefficient of thermal expansion (CTE) exhibits a step-like variation, making it less than optimal for mitigating thermal stress with epitaxial layers such as gallium arsenide. Therefore, it is necessary to explore simpler, more convenient, and more efficient methods for preparing gradient-distributed boron nitride / polyimide composite films. Although a large body of research has already provided information on the preparation of polyimide composite films, finding simple and convenient methods for preparing gradient-distributed boron nitride / polyimide composite films remains essential.

[0005] Therefore, developing a polyimide composite substrate with a continuous or stepped gradient structure, capable of achieving ultra-low CTE matching with the GaAs interface at low average filler content, high overall thermal conductivity, and excellent flexibility is crucial for promoting the development of flexible gallium arsenide solar cells. Summary of the Invention

[0006] This invention aims to overcome the shortcomings of the prior art by providing a gradient boron nitride / polyimide composite substrate, its preparation method, and its applications. This invention utilizes stainless steel ball milling beads in an alkaline environment to generate magnetic iron oxide / boron nitride composite magnetic nanosheets during the ball milling process of boron nitride nanosheets. This achieves hydroxylation and magnetization of the boron nitride nanosheets, and under magnetic field induction, a concentration gradient distribution of the nanosheets is formed from one side to the other within the film, resulting in a gradient boron nitride / polyimide composite substrate. This composite substrate possesses good mechanical properties, flexibility, thermal conductivity, and a low coefficient of thermal expansion, making it suitable for use as a flexible GaAs battery substrate. Without excessively compromising the film's flexibility and processability, it significantly improves the thermal matching with the GaAs epitaxial layer and the heat dissipation capacity of the device, thereby improving the reliability and lifespan of the battery. Compared to the unmagnetized boron nitride nanosheet approach, the gradient boron nitride / polyimide composite substrate of this invention further reduces the coefficient of thermal expansion while improving thermal conductivity.

[0007] The advantages of this invention are that it is very easy to achieve hydroxylation and magnetization of boron nitride nanosheets, with high yield, and the film performance improvement effect of high concentration boron nitride distribution on one side with low doping ratio, so that the gradient boron nitride / polyimide composite film has good mechanical properties and low coefficient of thermal expansion.

[0008] The objective of this invention can be achieved through the following methods: In a first aspect, the present invention provides a method for preparing a gradient boron nitride / polyimide composite substrate, comprising the following steps: S1. Hydroxylation and magnetization of boron nitride nanosheets: Boron nitride nanosheets were dispersed in an alkaline solution to obtain a boron nitride dispersion; the boron nitride dispersion was ball-milled with stainless steel ball milling beads to obtain a (brown) hydroxylated magnetic boron nitride suspension. S2. Preparation of hydroxylated magnetic boron nitride nanosheet solid powder: The hydroxylated magnetic boron nitride suspension was filtered, washed, and freeze-dried to obtain hydroxylated magnetic boron nitride nanosheet powder. S3. Preparation of hydroxylated magnetic boron nitride nanosheets / polyamic acid: hydroxylated magnetic boron nitride nanosheet powder was dispersed in a solvent and ultrasonically dispersed to obtain a hydroxylated magnetic boron nitride dispersion; then, diamine monomer and dianhydride monomer were added to the hydroxylated magnetic boron nitride dispersion and stirred to obtain a (brown) hydroxylated magnetic boron nitride nanosheet / polyamic acid solution. S4. Preparation of gradient boron nitride / polyimide composite film: Hydroxylated magnetic boron nitride nanosheets / polyamic acid solution are poured onto a (smooth) substrate and uniformly coated to obtain a boron nitride / polyamic acid film; a magnet is placed at the bottom of the substrate for magnetic adsorption treatment, and after drying, a high-temperature imidization treatment is performed to obtain a gradient boron nitride / polyimide composite substrate.

[0009] As one embodiment of the present invention, in step S1, the boron nitride nanosheets can be prepared by physical methods, chemical methods and solid-state methods.

[0010] In one embodiment of the present invention, in step S1, the alkaline solution is selected from one or more of NaOH solution, KOH solution, and LiOH solution; the concentration of the alkaline solution is 1.5-2.5 mol / L.

[0011] In one embodiment of the present invention, in step S1, the stainless steel grinding balls are made of 304 stainless steel and have a diameter of 3-5 mm; the ball-to-material ratio of the grinding balls is 60-80:1.

[0012] In one embodiment of the present invention, in step S1, the grinding jar used for the ball mill is made of 304 stainless steel. In some embodiments, the capacity of the grinding jar is 250 ml.

[0013] The magnetism of this invention is mainly due to the iron oxide produced by the use of stainless steel ball milling beads and the action of alkali, which possesses magnetic properties. If agate beads or zirconium beads are used, magnetic boron nitride cannot be obtained.

[0014] In one embodiment of the present invention, in step S1, the concentration of the boron nitride dispersion is 0.01-0.1 g / mL.

[0015] In one embodiment of the present invention, in step S1, the ball mill rotates at a speed of 100-300 rpm for 18-30 hours. The ball milling is performed using a planetary ball mill with an operating frequency of 33 Hz, bidirectional operation, and a switching time of 10 minutes.

[0016] In one embodiment of the present invention, in step S2, the washing is performed by washing with deionized water until the pH of the filtrate is neutral.

[0017] In one embodiment of the present invention, in step S2, the freeze-drying process takes 24 to 36 hours.

[0018] In one embodiment of the present invention, in step S3, the solvent includes N,N-dimethylacetamide.

[0019] In one embodiment of the present invention, in step S3, the concentration of the hydroxylated magnetic boron nitride dispersion is 0.001~0.03 mg / mL.

[0020] In one embodiment of the present invention, in step S3, the diamine monomer is selected from 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, bis[4-( [4-aminophenoxy]phenyl]sulfone, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)benzidine, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 1,3-diamino-2,4,5,6-tetrafluorobenzene, 4,4'-diaminocyclohexylmethane, 1,4-cyclohexanediamine, norbornene dimethylamine, and 1,3-cyclohexanedimethylamine are among one or more of these.

[0021] In one embodiment of the present invention, in step S3, the dianhydride monomer is selected from 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, pyromellitic dianhydride, asymmetric biphenyl dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride, and bisphenol A. The dianhydride is one or more of the following: diether dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 1S,2S,4R,5R-cyclohexanetetracarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 3,4,9,10-pyrenetetracarboxylic anhydride, triptenetetracarboxylic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9′-spirobisfluorene dianhydride (BDFDA), and 4,4′-dinaphthalene-1,1′,8,8′-tetracarboxylic anhydride.

[0022] In some embodiments, the molar amounts of the diamine monomer and the dianhydride monomer are equal; the sum of the masses of the diamine monomer and the dianhydride monomer is 10% of the mass of N,N-dimethylacetamide.

[0023] In one embodiment of the present invention, in step S3, the stirring is performed using magnetic stirring at a speed of 200-1500 rpm for 8-12 hours. The solid content of the hydroxylated magnetic boron nitride nanosheet / polyamic acid solution is 5-10 wt%.

[0024] In one embodiment of the present invention, in step S4, the substrate includes a glass plate; the coating is performed using a doctor blade with a depth of 500 μm.

[0025] In one embodiment of the present invention, in step S4, the magnet includes a neodymium magnet; the magnetic field strength of the magnetic adsorption treatment is 0.3-1.5 T (i.e., 300–1500 mT), and the time is 10-20 min. Preferably, it is 0.5-1.0 T.

[0026] In one embodiment of the present invention, in step S4, the drying process involves heating at 60, 90, and 120°C for 30 minutes each. This heating process pre-evaporates the solvent.

[0027] As one embodiment of the present invention, in step S4, the high-temperature imidization treatment is performed by heating at 150, 180, and 300°C for 50-70 minutes respectively.

[0028] This invention utilizes boron nitride nanosheets that undergo simultaneous hydroxylation and magnetization as functional fillers. During film formation, their magnetism is induced by an external magnetic field, causing them to migrate and accumulate directionally within a polyimide precursor (polyamic acid) solution. This naturally creates a BN concentration gradient distribution from one side of the film to the other in a one-step coating process. Subsequent thermal imidization yields the final gradient composite film.

[0029] Secondly, the present invention provides a gradient boron nitride / polyimide composite substrate obtained by the preparation method described above.

[0030] Thirdly, the present invention provides the use of the gradient boron nitride / polyimide composite substrate in the fabrication of flexible gallium arsenide solar cells or flexible gallium arsenide laser cells.

[0031] Fourthly, the present invention provides a flexible gallium arsenide solar cell, comprising an epitaxial functional layer and a flexible substrate, wherein the flexible substrate is the gradient boron nitride / polyimide composite substrate.

[0032] The inventor's prior art, "Preparation and Properties of Janus-Structured Polyimide / Boron Nitride Composite Thin Films," described a method involving ball milling of a boron nitride dispersion followed by acid washing with excess HCl solution. This resulted in the dissolution and removal of magnetic ions, preventing the generation of magnetism and magnetic field induction. Consequently, the boron nitride was uniformly distributed rather than gradient-distributed. This invention innovatively utilizes stainless steel beads that interact with an alkali during ball milling. Under high-energy ball milling, magnetic iron oxide / boron nitride composite magnetic nanosheets are generated. Under magnetic field induction, a gradient boron nitride / polyimide composite substrate is formed, reducing the coefficient of thermal expansion and significantly improving the thermal matching between the substrate and the GaAs epitaxial layer, while simultaneously enhancing the thermal conductivity of the battery.

[0033] Compared with the prior art, the present invention has the following beneficial effects: 1. Superior Thermomechanical Reliability: The gradient BN / PI composite film prepared in this invention has the highest BN nanosheet concentration on the side designated as the device growth interface (i.e., the side closer to the GaAs epitaxial layer), gradually decreasing towards the other side. This significantly reduces the coefficient of thermal expansion on the high-BN content side. Through this gradient transition CTE design, compared to the abrupt interface of the Janus structure, the thermal stress between the GaAs epitaxial layer and the polymer substrate can be released more smoothly, fundamentally reducing the risk of interface cracking in flexible gallium arsenide solar cells during thermal cycling and greatly improving the device's environmental tolerance and service life. Simultaneously, the low BN concentration on the flexible side preserves the good flexibility of polyimide, making the entire substrate both rigid and flexible.

[0034] 2. Excellent thermal management capabilities: The magnetic induction and gradient distribution of this invention help BN nanosheets form a more effective thermally conductive network in the in-plane direction. The gradient distribution and in-plane orientation of BN enable the composite film to achieve significantly improved in-plane thermal conductivity while maintaining overall flexibility. This provides a highly efficient heat dissipation channel for flexible GaAs solar cells, facilitating the rapid diffusion and dissipation of heat generated during cell operation along the substrate plane, reducing the cell's operating temperature, preventing hot spot formation, improving cell stability and efficiency, thereby maintaining high conversion efficiency and delaying performance degradation.

[0035] 3. Good balance of comprehensive performance: While achieving low CTE and high thermal conductivity, this invention maintains good mechanical strength, flexibility and certain light transmittance due to the adoption of gradient design and low overall filler load strategy, which fully meets the basic requirements of flexible solar cell substrates for bendability, lightweight and subsequent processing.

[0036] 4. Low dielectric constant and loss: The introduction of BN in this invention reduces CTE and also gives the composite substrate a lower dielectric constant and dielectric loss. This is beneficial to reducing parasitic capacitance at high frequencies and has a positive effect on the electrical performance of high-performance solar cells (especially multi-junction cells for space use).

[0037] 5. Simple process and easy integration: The preparation method of this invention is based on solution coating and magnetic field induction. The process is simple and has good compatibility with large-area, roll-to-roll flexible electronics manufacturing technology. It is easy to realize industrial production and provides a reliable substrate material solution for the low-cost manufacturing of high-performance flexible gallium arsenide solar cells. Attached Figure Description

[0038] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is a schematic diagram of the method of the present invention; Figure 2 This is a digital photograph of the polyimide composite film in Example 1; Figure 3 This is a scanning electron microscope image of the cross-section of the polyimide composite film in Example 1; Figure 4 This is a stress-strain curve of the polyimide composite film in Example 1; Figure 5 This is a graph showing the coefficient of thermal expansion of the polyimide composite film in Example 1; Figure 6 The images show photographs and cross-sectional topography of the flexible GaAs solar cell in Example 1; the left image is a photograph of the flexible GaAs solar cell, and the right image is a cross-sectional topography of the flexible cell. Figure 7 The full scan and high-resolution spectra of hydroxylated magnetic boron nitride in Example 1 are shown; where a is the XPS full scan, b is the B1s high-resolution spectrum, c is the N1s high-resolution spectrum, d is the O1s high-resolution spectrum, and e is the Fe2p high-resolution spectrum. Detailed Implementation

[0039] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, providing detailed implementation methods and specific operating procedures, which will help those skilled in the art to further understand the present invention. It should be noted that the scope of protection of the present invention is not limited to the following embodiments; any adjustments and improvements made under the concept of the present invention are all within the scope of protection of the present invention.

[0040] Example 1 The method for preparing the gradient-distributed boron nitride / polyimide composite film described in this embodiment includes the following steps: 1. At room temperature, 3g of boron nitride nanosheets were dispersed in 30ml of 2mol / L NaOH solution and loaded together with 210g of stainless steel (304) grinding balls into a 250ml stainless steel (304) ball milling jar. The ball milling jar was placed in a planetary ball mill and milled at 200rpm for 24h to obtain a brown hydroxylated magnetic boron nitride suspension.

[0041] 2. The hydroxylated magnetic boron nitride suspension obtained from the above reaction was filtered, washed with deionized water, and finally freeze-dried for 24 hours to obtain dried hydroxylated magnetic boron nitride nanosheets.

[0042] 3. Disperse 1.5g of the dried hydroxylated magnetic boron nitride nanosheets in 50mL of N,N-dimethylacetamide and sonicate for 0.5h to obtain a uniform hydroxylated magnetic boron nitride dispersion. Then add 2.02g of 4,4'-diaminodiphenyl ether to the above solution, followed by gradually adding 2.98g of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride. Stir magnetically at 500rpm for 8-12h to obtain a brown boron nitride / polyamic acid solution with a solid content of 10wt%.

[0043] 4. Pour 5-10 mL of the boron nitride / polyamic acid solution obtained from the above reaction onto a smooth glass plate. Use a doctor blade with a depth of 500 μm to uniformly coat the solution to obtain a boron nitride / polyamic acid film. Then, place a neodymium magnet (magnetic field strength of 0.5-1.0 T) at the bottom of the glass plate and perform magnetic adsorption treatment for 10 min. Immediately afterwards, place the glass plate in a vacuum drying oven and heat at 60, 90, and 120 °C for 0.5 h respectively to pre-evaporate the solvent. Then, heat at 150, 180, and 300 °C for 1 h respectively for high-temperature imidization treatment. After naturally cooling to room temperature, immerse the glass plate in water. The film detaches from the glass plate, resulting in a gradient-distributed boron nitride / polyimide composite film.

[0044] Figure 1 This is a flowchart illustrating the preparation process of the gradient-distributed boron nitride / polyimide composite film of the present invention. The preparation method is simple and convenient. Figure 2 The digital photograph of the obtained polyimide composite film shows that the surface of the polyimide film is smooth and flat. Figure 3 The electron microscope image shows the cross-sectional morphology of the polyimide composite film. It can be seen that the boron nitride nanosheets inside the polyimide film exhibit a gradient distribution and are tightly packed between layers. Figure 4 The stress-strain curve of the polyimide composite film is shown in the figure. The mechanical modulus is 2.3 GPa, indicating that the gradient boron nitride / polyimide composite film of the present invention has good mechanical properties. Figure 5 The figure shows the coefficient of thermal expansion curve of the polyimide composite film. The coefficient of thermal expansion is 14 ppm / K, indicating that the gradient boron nitride / polyimide composite film of the present invention has a low coefficient of thermal expansion.

[0045] Figure 6 The images show a flexible GaAs solar cell (left) and a cross-sectional morphology diagram (right), demonstrating that no visible cracks or peeling were observed on the surface and interface of the flexible cell.

[0046] Figure 7 The full scan and high-resolution spectra of hydroxylated magnetic boron nitride indicate that in addition to B and N elements, it also contains Fe and O elements, confirming that hydroxylated magnetic boron nitride contains magnetic iron oxides and no other impurity elements.

[0047] Example 2 The steps are the same as in Example 1, except that the amount of dried hydroxylated magnetic boron nitride nanosheets is changed to 2.5g, and the mechanical modulus of the prepared polyimide composite film is increased by 20% and the coefficient of thermal expansion is reduced by 15%.

[0048] Example 3 The steps are the same as in Example 1, except that the duration of the neodymium magnet magnetic adsorption treatment is changed to 20 min, which increases the mechanical modulus of the prepared polyimide composite film by 10% and reduces the coefficient of thermal expansion by 8%.

[0049] Example 4 The steps are the same as in Example 1, except that the amount of N,N-dimethylacetamide is changed to 100 mL, the solid content of the boron nitride / polyamic acid solution is changed to 5 wt%, the mechanical modulus of the prepared polyimide composite film is reduced by 30%, and the coefficient of thermal expansion is increased by 20%.

[0050] Example 5 The steps are the same as in Example 1, except that the NaOH solution in step 1 is replaced with a KOH solution. Experiments have verified that using KOH solution instead of NaOH solution also yields a brown hydroxylated magnetic boron nitride suspension, and a gradient-distributed boron nitride / polyimide composite film can be successfully prepared. This is because both KOH and NaOH are strong bases, and under the action of stainless steel ball milling beads, they can react with stainless steel to generate magnetic iron oxides, thereby achieving the hydroxylation and magnetization of boron nitride nanosheets.

[0051] Conclusion: Example 5 shows that the objectives of this invention can also be achieved using KOH solution, but the composite film prepared using KOH solution shows slightly less improvement in mechanical modulus (2.1 GPa) and coefficient of thermal expansion (16 ppm / K) compared to Example 1 using NaOH solution. This may be attributed to slight differences in the reactivity of KOH with stainless steel or the magnetic properties of the products, resulting in slightly different magnetic field-induced nanosheet migration efficiencies. Nevertheless, this example demonstrates the universality of the technical solution of this invention, namely, that various strongly alkaline solutions can be used to achieve the hydroxylation and magnetization of boron nitride nanosheets, thereby obtaining composite films with gradient structures.

[0052] Using the gradient BN / PI composite film obtained in Example 1 above as a flexible substrate, the following simulation or experimental verifications were performed for gallium arsenide solar cell applications: 1) Thermal cycling reliability test: The prepared composite film was compared with a standard commercial PI film (such as Kapton). After attaching a thin layer of GaAs material to its surface via epitaxial growth or bonding process, a thermal cycling test (e.g., 2000 cycles) from -65°C to 150°C was performed. The test results showed that the GaAs layer of the sample based on the gradient substrate of this invention did not exhibit visible cracks or peeling. Figure 6 In contrast, samples based on commercial PI substrates developed microcracks after approximately 1000 cycles and exhibited large-area delamination after 1500 cycles. This demonstrates that the gradient substrate of this invention significantly improves thermomechanical reliability.

[0053] 2) Heat dissipation performance simulation: Finite element analysis was used to simulate the temperature distribution of micro GaAs cells using the composite film of this invention and ordinary PI film as substrates under the same illumination conditions. The simulation results show that under standard AM1.5G illumination, the cell using the substrate of this invention has a maximum operating temperature of 62℃, which is 16℃ lower than the cell using an ordinary PI substrate (maximum temperature 78℃), and the temperature distribution is more uniform.

[0054] 3) Preliminary Photovoltaic Performance Testing: In the actually fabricated flexible GaAs solar cell device, its initial efficiency was monitored, and its output power decay rate was tested under continuous illumination. Preliminary test data showed that the initial efficiency of the cell using the substrate of this invention was 28.5%, and the efficiency decay rate was 3.2% after 1000 hours of continuous operation; while the control cell using a conventional PI substrate had an initial efficiency of 27.8%, and an efficiency decay rate of 8.5% under the same conditions. This confirms the positive effect of the substrate of this invention on improving cell stability.

[0055] Comparative Example 1 The preparation method of this comparative example is basically the same as that of Example 1, except that in step 1, an excess of HCl solution is added to the hydroxylated magnetic boron nitride suspension and heated and stirred for 4 h.

[0056] Table 1

[0057] As shown in Table 1, in Comparative Example 1, after ball milling the boron nitride dispersion, acid washing with an excess of HCl solution was performed, which caused the magnetic ions to be dissolved and washed away, making it impossible to generate magnetism and magnetic field induction. The boron nitride was uniformly distributed rather than gradient distributed, which ultimately resulted in its thermal expansion coefficient being higher than that of Example 1 and its heat dissipation performance being worse than that of Example 1.

[0058] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a gradient boron nitride / polyimide composite substrate, characterized in that, Includes the following steps: S1. Hydroxylation and magnetization of boron nitride nanosheets: Boron nitride nanosheets were dispersed in an alkaline solution to obtain a boron nitride dispersion; the boron nitride dispersion was ball-milled with stainless steel ball milling beads to obtain a hydroxylated magnetic boron nitride suspension. S2. Preparation of hydroxylated magnetic boron nitride nanosheet solid powder: The hydroxylated magnetic boron nitride suspension was filtered, washed, and freeze-dried to obtain hydroxylated magnetic boron nitride nanosheet powder. S3. Preparation of hydroxylated magnetic boron nitride nanosheets / polyamic acid: hydroxylated magnetic boron nitride nanosheet powder is dispersed in a solvent and ultrasonically dispersed to obtain a hydroxylated magnetic boron nitride dispersion; then, diamine monomer and dianhydride monomer are added to the hydroxylated magnetic boron nitride dispersion, and stirred to obtain a hydroxylated magnetic boron nitride nanosheet / polyamic acid solution. S4. Preparation of gradient boron nitride / polyimide composite film: Hydroxylated magnetic boron nitride nanosheets / polyamic acid solution are poured onto the substrate and uniformly coated to obtain boron nitride / polyamic acid film; a magnet is placed at the bottom of the substrate for magnetic adsorption treatment, and after drying, high-temperature imidization treatment is performed to obtain gradient boron nitride / polyimide composite substrate.

2. The preparation method according to claim 1, characterized in that, The alkaline solution is selected from one or more of NaOH solution, KOH solution, and LiOH solution; the concentration of the alkaline solution is 1.5-2.5 mol / L.

3. The preparation method according to claim 1, characterized in that, In step S1, the stainless steel milling balls are made of 304 stainless steel and have a diameter of 3-5 mm; the ball-to-material ratio of the milling process is 60-80:1; the milling speed is 100-300 rpm and the time is 18-30 h; the concentration of the boron nitride dispersion is 0.01-0.1 g / mL.

4. The preparation method according to claim 1, characterized in that, In step S3, the solvent includes N,N-dimethylacetamide; the concentration of the hydroxylated magnetic boron nitride dispersion is 0.001~0.03 mg / mL; and the solid content of the hydroxylated magnetic boron nitride nanosheet / polyamic acid solution is 5-10 wt%.

5. The preparation method according to claim 1, characterized in that, In step S3, the diamine monomer is selected from 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]propane ... The following are one or more of the following: 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)benzidine, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 1,3-diamino-2,4,5,6-tetrafluorobenzene, 4,4'-diaminocyclohexylmethane, 1,4-cyclohexanediamine, norbornene dimethylamine, and 1,3-cyclohexanedimethylamine.

6. The preparation method according to claim 1, characterized in that, In step S3, the dianhydride monomer is selected from 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, pyromellitic dianhydride, asymmetric biphenyl dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride, and bisphenol A. It is one or more of the following: diether dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 1S,2S,4R,5R-cyclohexanetetracarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 3,4,9,10-pyrenetetracarboxylic anhydride, triptenetetracarboxylic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9′-spirobisfluorene dianhydride, and 4,4′-dinaphthalene-1,1′,8,8′-tetracarboxylic anhydride.

7. The preparation method according to claim 1, characterized in that, In step S4, the magnet includes a neodymium magnet; the magnetic field strength of the magnetic adsorption treatment is 0.3-1.5 T, and the time is 10-20 min; the high-temperature imidization treatment is: heating at 150, 180, and 300℃ for 50-70 min respectively.

8. A gradient boron nitride / polyimide composite substrate obtained by the preparation method according to any one of claims 1-7.

9. The use of the gradient boron nitride / polyimide composite substrate as described in claim 8 in the fabrication of flexible gallium arsenide solar cells or flexible gallium arsenide laser cells.

10. A flexible gallium arsenide solar cell, characterized in that, It includes an epitaxial functional layer and a flexible substrate, wherein the flexible substrate is the gradient boron nitride / polyimide composite substrate as described in claim 8.